Near vertical iso-illite-crystallinity surfaces cross-cut the recumbent fold structure of the Morcles nappe, Swiss Alps - Burkhard, Martin; Goy-Eggenberger, D. (My University, 2001)
Metamorphic isograd surfaces are mapped within the Morcles nappe using illite crystallinity (IC) and (clay-) mineral parageneses in 268 samples. The diagenesis-anchizone and the anchizone-epizone boundaries are nearly vertical surfaces which crosscut the present-day recumbent fold nappe structure. Frontal parts of the nappe are diagenetic (Tmax <200°C) whereas rear parts both in the normal and inverted limb are epizonal (Tmax >300°C). We demonstrate that the calcite content of shales, marls or limestones has no influence on the average IC. Deviations of individual samples from the mean IC of any given diagenetic and lower anchizonal site are very large, however, without it being possible to associate deviations with any obvious rock parameter. The standard deviations of populations of IC values decrease strongly with increasing metamorphic grade (toward smaller IC values). Mapping the diagenesis-anchizone boundary requires a much larger sampling effort than the same exercise for the anchizone-epizone boundary.